2018
DOI: 10.1101/278143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphorylation by CK2 Regulates MUS81/EME1 in Mitosis and After Replication Stress

Abstract: The MUS81 complex is crucial for preserving genome stability through the resolution of branched DNA intermediates in mitosis. However, untimely activation of the MUS81 complex in S-phase is dangerous. Little is known about the regulation of the human MUS81 complex and how deregulated activation affects chromosome integrity. Here, we show that the CK2 kinase phosphorylates MUS81 at Serine 87 in late-G2/mitosis, and upon mild replication stress. Phosphorylated MUS81 interacts with SLX4, and this association prom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 48 publications
4
25
0
Order By: Relevance
“…Thus, the isolated MUS81-EME1 and MUS81-EME2 proteins are identical in substrate recognition and endonuclease activities, while their distinct roles in cells could arise See also Figures S4 and S5. ll Article from the cellular temporal controls, such as phosphorylation or association with other regulators (Palma et al, 2018;Princz et al, 2017;Sebesta et al, 2017;Waizenegger et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the isolated MUS81-EME1 and MUS81-EME2 proteins are identical in substrate recognition and endonuclease activities, while their distinct roles in cells could arise See also Figures S4 and S5. ll Article from the cellular temporal controls, such as phosphorylation or association with other regulators (Palma et al, 2018;Princz et al, 2017;Sebesta et al, 2017;Waizenegger et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…MUS81 has also been implicated in other cellular transactions, such as BIR and alternative-lengthening of telomeres (ALT) [92,99]. Apart from CDK1-mediated activation, MUS81 can also be phosphorylated by CK2 at Ser87 in G2/M and is required to maintain genome stability following RS [113]. Thus, CK2 and CDK1 phosphorylation of MUS81 in G2/M might be pre-requisite for MiDAS initiation.…”
Section: Mitotic Dna Repair Synthesis or Break-induced Mitosis Dna Synthesismentioning
confidence: 99%
“…Given the proposed important role of CDK1 for MiDAS, one cannot yet rule out that the same repair reaction might have begun prior to mitosis, namely in late G2, if normal CDK1 activity was not suppressed. Furthermore, CK2-mediated phosphorylation at Ser87 of MUS81 is also seen in late G2 cells, which may also imply that MUS81's activation could have initiated prior to mitotic onset, but further investigation is required [113].…”
Section: Mitotic Dna Repair Synthesis or Break-induced Mitosis Dna Synthesismentioning
confidence: 99%
“…Abrogation of phosphorylation through expression of an unphosphorylable S87A-MUS81 allele impairs only mitotic resolution of DNA intermediates, making this form of MUS81 a separation-offunction mutant (24).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that CK2-dependent phosphorylation of MUS81 at S87 stimulates association with SLX4 in late G2/M and regulates the function of the MUS81/EME1 complex in mitosis (24). Abrogation of phosphorylation through expression of an unphosphorylable S87A-MUS81 allele impairs only mitotic resolution of DNA intermediates, making this form of MUS81 a separation-of-function mutant (24).…”
Section: Introductionmentioning
confidence: 99%